Mothers’ Perceptions of the Role of Preschool in the Development of Self-Regulation Skills in Children - Sarwat Nauman; Mahwish Ali Baber (International Journal of Experiential Learning & Case Studies, 2020)
It is considered agreed upon that self-regulation is an important determinant of academic success. Studies suggest that self-regulation begins to develop early in childhood, that is, the pre-school years. This study attempts to find out if mothers of three-year-old children consider it necessary to send their children to preschool and if they consider preschools to be satisfactorily developing their children’s self-regulation skills. Thus, 20 semi-structured qualitative interviews from mothers of preschoolers, belonging to the upper-middle class of Karachi were conducted. Findings indicate that mothers generally deem preschool to be a necessary activity based center for their children, where they could develop trusting relationships with their peers and teachers and learn to regulate their emotions, thereby developing the overall self-regulation skills in them. Interestingly, a major underlying source of this perception is the demographic changes including the prevalence of more nuclear families and the increasing trend of working mothers in Pakistani society